Eksploitasi Anak di Ranah Budaya: Studi Kasus Tradisi Pacu Kuda di Gayo - Mashury, Davi abdullah (Jurnal Seni Urban dan Industri Budaya, 2024)
The tradition of horse racing has been going on for a long time in several regions of the archipelago. One of them is in the Gayo Highlands, Aceh. Child exploitation in the cultural realm of horse racing traditions has been going on for a long time and generations. Forms of exploitation experienced by child jockeys include social exploitation, economic exploitation, and physical exploitation. This research focuses on the exploitation of children in the realm of traditional culture, especially horse racing in Gayo Highlands. The research method used is an ethnographic method with a cultural studies approach. This study aims to analyze cultural traditions that are considered no longer by current values and are no longer relevant to current conditions. By documenting problems in the racehorse tradition, it is hoped that it can answer the anxiety and problems of children in the cultural realm who experience exploitation with the hope of having an impact on the sense of security for child jockeys, Avoiding exploitation, and remaining part of the preservation and promotion of cultural traditions, arts, and folk games.________________________________________________________Tradisi pacu kuda sudah berlangsung lama di sejumlah daerah di Nusantara. Salah satunya di daerah Dataran Tinggi Gayo, Aceh. Eksploitasi anak di ranah budaya tradisi pacuan kuda sudah terjadi lama dan secara turun-temurun. Bentuk eksploitasi yang dialami oleh para joki anak meliputi, eksploitasi sosial, eksploitasi ekonomi serta eksploitasi fisik. Penelitian ini terfokus pada eksploitasi anak di ranah kebudayaan tradisi, khususnya pacuan kuda di Dataran Tinggi Gayo. Metode penelitian yang digunakan adalah metode etnografi dengan pendekatan cultural studies. Penelitian ini bertujuan menganalisis budaya tradisi yang dianggap sudah tidak sesuai dengan nilai-nilai yang berlaku sekarang dan tidak relevan lagi dengan kondisi sekarang. Dengan mendokumentasikan masalah dalam tradisi kuda pacu, 17 diharapkan dapat menjawab kegelisahan dan persoalan anak di ranah budaya yang mengalami eksploitasi dengan harapan mampu memberikan dampak terhadap rasa aman bagi para joki anak, terhindar dari eksploitasi, serta tetap menjadi bagian dalam pelestarian dan pemajuan kebudayaan tradisi, seni dan permainan rakyat.